Influence of extraneous waters on the quality and loads of pollutants in wastewater discharged into the treatment plant - Kaczor Grzegorz B.; Chmielowski Krzysztof; Bugajski Piotr (Journal of Water and Land Development, 2017)
The aim of the study was to analyze an influence of an inflow penetrating into two selected small sewerage systems during a rainy weather on pollutant concentration and load in raw sewage. Studies were conducted in 2010–2015 on two small sewerage systems in Małopolska province. The studies confirmed that the inflow penetrating into the sewerage systems resulted in a decrease of pollutant concentrations in sewage. However, they also showed that this dilution was not constant for all types of pollutants. The most important outcome of the study was demonstrating that despite its diluting effect on pollutants, the intense inflow into a sewerage system resulted in an increase of a sewage pollutant load. This increase was not regular, but it was rising dramatically when the inflow share in sewage exceeded 50%. The study indicated that the inflow penetrating into the sewerage system should not be disregarded, as it actually presented a significant threat to the wastewater treatment process and in consequence to the quality of recipient waters.